Bibliometric evaluation of Forensic Science International as a scholarly journal within the subject category legal medicine - Jones, Alan Wayne (Forensic science international. Synergy, 2023)
This article presents a bibliometric evaluation of Forensic Science International (FSI) as a scholarly journal within the "legal medicine" subject category. Citation data were retrieved from Science Citation Index (SCI) and Journal Citation Reports (JCR), both of which are part of the Web-of-Science (WOS) database. The most cited articles in FSI were identified along with the most prolific authors. The current journal impact factor (JIF) of FSI is 2.2, which was in good agreement with the 5-year JIF of 2.3. FSI was ranked fourth among 17 journals within the legal medicine subject category. Since 1979, a total of 209 FSI articles were cited over 100 times and the H-index for times cited was 125. Although widely used in academia, bibliometric methods might also prove useful in jurisprudence, such as when evaluating the research and publications of people proposed as expert witnesses.This article presents a bibliometric evaluation of Forensic Science International (FSI) as a scholarly journal within the "legal medicine" subject category. Citation data were retrieved from Science Citation Index (SCI) and Journal Citation Reports (JCR), both of which are part of the Web-of-Science (WOS) database. The most cited articles in FSI were identified along with the most prolific authors. The current journal impact factor (JIF) of FSI is 2.2, which was in good agreement with the 5-year JIF of 2.3. FSI was ranked fourth among 17 journals within the legal medicine subject category. Since 1979, a total of 209 FSI articles were cited over 100 times and the H-index for times cited was 125. Although widely used in academia, bibliometric methods might also prove useful in jurisprudence, such as when evaluating the research and publications of people proposed as expert witnesses.